Mechanical Characterization and Water Absorption Behaviour of Interwoven Kenaf/PET Fibre Reinforced Epoxy Hybrid Composite - Yakubu Dan-mallam; Tan Wei Hong; Mohd Shukry Abdul Majid (International Journal of Polymer Science)
The development of interwoven fabric for composite production is a novel approach that can be adopted to address the challenges of balanced mechanical properties and water absorption behaviour of polymer composites. In this paper, kenaf and PET (polyethylene terephthalate) fibre were selected as reinforcing materials to develop the woven fabric, and low viscosity epoxy resin was chosen as the matrix. Vacuum infusion process was adopted to produce the hybrid composite due to its superior advantages over hand lay-up technique. The weight percentage composition of the Epoxy/kenaf/PET hybrid composite was maintained at 70/15/15 and 60/20/20, respectively. A significant increase in tensile strength and elastic modulus of approximately 73% and 53% was recorded in relation to neat epoxy. Similarly, a substantial increase in flexural, impact, and interlaminar properties was also realized in relation to neat epoxy. This enhancement in mechanical properties may be attributed to the interlocking structure of the interwoven fabric, individual properties of kenaf and PET fibres, strong interfacial bonding, and resistance of the fibres to impact loading. The water absorption of the composites was studied by prolonged exposure in distilled water, and the moisture absorption pattern was found to follow Fickian behaviour.